Implementation of the Performance Allowance Policy at the Regional Inspectorate Office of North Sulawesi Province - Maramis, Deysje F.; Tumbel, Goinpeace H.; Bogar, Wilson (Technium Social Sciences Journal, 2025)
The purpose of this study was to analyze the implementation process of the performance allowance policy at the Regional Inspectorate Office of North Sulawesi Province, identify obstacles faced during its implementation, and assess its impact on employee performance. This research used a descriptive qualitative approach using data collection methods such as in-depth interviews, observation, and document review. Analysis was conducted using thematic analysis techniques to identify patterns and main themes related to the implementation of the performance allowance policy. The results showed that the performance allowance policy at the Regional Inspectorate Office of North Sulawesi Province had been implemented in accordance with applicable regulations. However, several challenges were identified, including budget constraints, resistance from some employees, and a lack of understanding of the performance appraisal mechanism. The impact of this policy on employee performance varies. Some employees experienced increased motivation and productivity, while others were less affected by the policy. Factors such as transparency in performance evaluation and clarity in reward mechanisms play an important role in the effectiveness of performance allowance policies. This study recommends improvements in policy communication, increased socialization of the performance allowance mechanism, and continuous evaluation to ensure that the policy is more effective and fair for all employees.